2020
DOI: 10.1002/eng2.12154
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of cuttings transport of nanoparticle‐based drilling fluid

Abstract: Cuttings transportation from the drill bit, through the annulus, to the surface is one of the most important functions performed by drilling fluid. The prediction of drilling fluid's performance to transport cuttings in the annulus is very complex task due to the presence of numerous parameters. Nanoparticles (NPs) have been recently introduced into drilling fluid to engineer its properties and enhance its performance. Nevertheless, the lifting capacity has not been sufficiently investigated. The understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The outcomes acquired by this model showed that in horizontal annulus and low flow rates of liquid, the pipe rotation becomes more effective by increasing the air flow rate, while the efficiency of cutting transport with the aerated mud reduces by increasing the inclination. Al-Yasiri et al [20] studied the influence of Nanoparticles and the effects of various parameters such as flow rate, pipe rotation, drilling fluids rheology, cuttings density, concentration, shape, and drilling fluids-cuttings particle coupling regimes on the cuttings transport in a vertical wellbore. It showed that the cuttings transport process and fluid viscosity can be significantly enhanced by addition nanomaterial to the fluid, and the process is highly effected by cuttings characteristics such as in shape, situ concentration, and density.…”
Section: Misan Journal Of Engineering Sciencesmentioning
confidence: 99%
“…The outcomes acquired by this model showed that in horizontal annulus and low flow rates of liquid, the pipe rotation becomes more effective by increasing the air flow rate, while the efficiency of cutting transport with the aerated mud reduces by increasing the inclination. Al-Yasiri et al [20] studied the influence of Nanoparticles and the effects of various parameters such as flow rate, pipe rotation, drilling fluids rheology, cuttings density, concentration, shape, and drilling fluids-cuttings particle coupling regimes on the cuttings transport in a vertical wellbore. It showed that the cuttings transport process and fluid viscosity can be significantly enhanced by addition nanomaterial to the fluid, and the process is highly effected by cuttings characteristics such as in shape, situ concentration, and density.…”
Section: Misan Journal Of Engineering Sciencesmentioning
confidence: 99%
“…Further, the initial and boundary conditions are set, i.e. the direction of the entry of the drilling mud into the drill string and its exit through the annular space, the flow rate of the drilling mud is set, the parameters of the mud -viscosity, density, type of mud, rheological model etc [1].…”
Section: Well Model Creation In «Ansys Cfx» Softwarementioning
confidence: 99%
“…The drilling process is said to be successful if the cuttings can be lifted to the surface. Therefore, the velocity of the drilling fluid in the annular must be greater than the velocity at which the cuttings falls, so that the velocity at which the cutting rises is obtained from the following equation [6], [12], [14]:…”
Section: Introductionmentioning
confidence: 99%